Floating Crossing Raft (RAP) as a Means of Transportation for Coastal Communities in East Luwu Regency - Muhammad Fajar Firmansyah; Mardiana E. Fachry; Andi Adri Arief; Firman Firman (PONGGAWA : Journal of Fisheries Socio-Economic, 2025)
This study analyzes the role of crossing boats (RAP) on the mobilization of coastal communities between Nuha Village and Sorowako Village in East Luwu Regency. Floating rafting boats (RAP) are one of the crossing transportation used since ancient times in Lake Matano which is used by the community on average 500 people per day to cross from Sorowako Port to Nuha Port and vice versa. The cruise from Sorowako to Nuha is taken with a cruise time of two to three hours depending on the amount of cargo carried. The location is determined purposively with the consideration that at the location there is a crossing pier that has a boat called a Floating Crossing Raft (RAP) which mobilizes the community between Nuha Village and Sorowako Village.Crossing boats (RAP) play an important role in supporting community mobility between Nuha Village and Sorowako Village, East Luwu Regency. As the main means of transportation connecting the two villages, boats (RAPs) allow for faster distribution of goods and services, including fish catches, agricultural products, and other basic necessities. Boats (RAPs) play an important role in improving travel time and cost efficiency, particularly through the management of infrastructure and transportation around Lake Matano. With the existence of boats (RAP), access to the lake and the surrounding area can be improved, thereby supporting tourism activities and increasing the attractiveness of this destination for local and foreign tourists. In addition, boats (RAPs) also contribute to the management of fishery resources through better arrangements for fishing activities and the preservation of endemic species, such as butini and opudi.